2023
DOI: 10.3389/fclim.2022.949411
|View full text |Cite
|
Sign up to set email alerts
|

Integrating biological and chemical CO2 sequestration using green microalgae for bioproducts generation

Abstract: Microalgae cultivation is considered an attractive negative emission technology (NET) due to its ability to remove carbon dioxide (CO2) from the atmosphere as well as from flue gases. Moreover, some microalgae can uptake dissolved carbon in the form of bicarbonate (HCO3-) and grow well by removing nutrients from various wastewater effluents without competing with freshwater resources. Conventional carbon mineralization is another NET where carbon is fixed into carbonate minerals such as calcite (CaCO3), magnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Eustance et al [39] reported similar results at laboratory scale; they observed an extreme shift in pH when the strains were grown at high ammonium concentrations (i.e., 2.94 mM ammonium chloride) in unbuffered medium, which triggered growth inhibition and chlorophyll degradation. Furthermore, the results from our previous work [40] showed that mineral carbonates such as sodium carbonate (Na2CO3) or MgCO3.3H2O (nesquehonite) can buffer the pH well and maintain it within acceptable algae physiological values. Biomass growth over time was evaluated by measuring fluorescence (fluorescence units, FU) and ash-free dry weight (AFDW, in g/L).…”
Section: Exploratory Run (Er): Operating Conditions and Performancementioning
confidence: 99%
“…Eustance et al [39] reported similar results at laboratory scale; they observed an extreme shift in pH when the strains were grown at high ammonium concentrations (i.e., 2.94 mM ammonium chloride) in unbuffered medium, which triggered growth inhibition and chlorophyll degradation. Furthermore, the results from our previous work [40] showed that mineral carbonates such as sodium carbonate (Na2CO3) or MgCO3.3H2O (nesquehonite) can buffer the pH well and maintain it within acceptable algae physiological values. Biomass growth over time was evaluated by measuring fluorescence (fluorescence units, FU) and ash-free dry weight (AFDW, in g/L).…”
Section: Exploratory Run (Er): Operating Conditions and Performancementioning
confidence: 99%